1992
DOI: 10.1148/radiology.183.1.1549675
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of benign from malignant superficial lymphadenopathy: the role of high-resolution US.

Abstract: Ultrasonography has proved a valuable tool for the detection of enlarged lymph nodes; however, differentiation between benign and malignant nodal disease remains a problem. High-frequency probes with improved spatial and contrast resolution display superficial nodes to advantage and also show the internal structure of the nodes. Ninety-four superficial nodes in patients with suspected nodal disease were examined by using 7.5-MHz probes to evaluate longitudinal-transverse diameter ratio (L/T), the central hilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
342
8
33

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 522 publications
(408 citation statements)
references
References 0 publications
25
342
8
33
Order By: Relevance
“…The widely-accepted US criteria for identifying a malignant LN includes round shape (L/ S<2), absence of hyperechoic hilum, peripheral or mixed vascular patterns (Vassallo et al, 1992; Ahuja and Ying, :http://dx.doi.org/10.7314/APJCP.2014.15.13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The widely-accepted US criteria for identifying a malignant LN includes round shape (L/ S<2), absence of hyperechoic hilum, peripheral or mixed vascular patterns (Vassallo et al, 1992; Ahuja and Ying, :http://dx.doi.org/10.7314/APJCP.2014.15.13…”
Section: Discussionmentioning
confidence: 99%
“…A node with a ratio of long to short diameter (L/S) <2 was defined as round shape, and a ratio of L/S≥2 as oval shape. The widely-accepted US criteria for identifying a malignant LN includes round shape (L/S<2), absence of hyperechoic hilum, peripheral or mixed vascular patterns (Vassallo et al, 1992;Ahuja and Ying, 2003). LNs who met one of the above criteria will do RTE for further diagnosis.…”
Section: Ultrasound Techniquesmentioning
confidence: 99%
“…However, the US study by Vassallo et al (1992) and a more recent in vitro study using high-resolution CT by Uematsu et al (2001) have shown that nodal shape, that is, a longitudinal by transverse axis ratio of less than 2, and abnormal morphology of the cortex with a thickness of more than 2 mm are the two most reliable criteria in predicting malignancy in vivo. We adopted these criteria in our study to identify abnormal nodes and selectively biopsy them.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal lymph node has a thickened or eccentrically bulging cortex and a diminished or absent hilum (Figs 3-5) (22,23). The thickened cortex should be the target at biopsy.…”
Section: Abnormal Lymph Nodementioning
confidence: 99%